2017
DOI: 10.1038/srep43831
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of atrazine and copper using polyacrylic acid-functionalized magnetic ordered mesoporous carbon from water: adsorption mechanism

Abstract: Highly efficient simultaneous removal of atrazine and Cu(II) was accomplished using synthesized polyacrylic acid-functionalized magnetic ordered mesoporous carbon (P-MMC) as compared to magnetic ordered mesoporous carbon (MMC) and ordered mesoporous carbon (OMC). The mutual effects and interactive mechanism of their adsorption onto P-MMC were investigated systematically by binary, preloading and thermodynamic adsorption procedures. In both binary and preloading systems, the adsorption of atrazine was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…This is in agreement with reports of Tharaneedhar et al [42]. Differences in energy natures and affinities of adsorbents could be linked to the modification of surface chemistry and reduction in particle sizes [29,47,55,60].…”
Section: Adsorption Thermodynamicssupporting
confidence: 92%
“…This is in agreement with reports of Tharaneedhar et al [42]. Differences in energy natures and affinities of adsorbents could be linked to the modification of surface chemistry and reduction in particle sizes [29,47,55,60].…”
Section: Adsorption Thermodynamicssupporting
confidence: 92%
“…The amount of atrazine adsorbed by the sample slightly increased in the presence of high NaCl concentration, and the increase of NaCl concentration had a little positive effect on the adsorption performance of atrazine onto ACs, as shown in Figure 6a. The possible reason was that the H-bond was formed between the water clusters and the H 2 O molecules, and then broke at the high concentration of NaCl, resulting in the appearing of the hydrophobic functional groups, which might improve the adsorption of atrazine by increasing amounts of NaCl [15].…”
Section: Resultsmentioning
confidence: 99%
“…For example, atrazine removal using ACs from wheat straw is via forming the π bond with atrazine in the adsorption process [11]; atrazine removal using ACs from corn stalks, poultry, rice straws, and pig manures is influenced mainly by the functional groups, which has small surface areas [12,14]. When atrazine coexists with Cu (II) in co-solution, the Cu (II) complexes can shield the hydrophobic and hydrophilic sites (carboxyl and hydroxyl) of atrazine adsorption [15]. However, the atrazine wastewater usually contains a variety of pollutants in a nature environment, and few studies had reported the effect of different substances in co-solution on the adsorption behavior of atrazine onto different adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods, such as advanced oxidation, biological treatment, electrochemical technologies, and adsorption, have been widely used to remove heavy metals from wastewater. [3][4][5][6] The adsorption technology is a preferred approach because of its safety, efficiency, and economic feasibility; moreover, it can be performed using low-cost sorbents in the adsorption process. 7 Biochar is the most popular sorbent in the sorption process, and many studies have been carried out on biochar.…”
Section: Introductionmentioning
confidence: 99%